PERANCANGAN VIDEO PROMOSI WISATA UNTUK PENGEMBANGAN WISATA DAERAH BERBASIS CERITA RAKYAT DI KABUPATEN WAJO - Masdiana, Masdiana; Kuswarini, Prasuri; Hasyim, Muhammad (E-Amal: Jurnal Pengabdian Kepada Masyarakat, 2024)
Tourism, namely narrative-based tourism. Through this concept, it is hoped that regional tourism potential can be further developed. Keera District in Wajo Regency has many folk tales that can be introduced. Supported by the existing natural beauty, of course these two things are a big asset in developing folklore-based tourism in this area. However, the existence of these two big capitals needs attention through tourism promotion. One form of effective promotion today is through uploading videos on social media. For this reason, an attractive video design is needed to present promotional media that can attract people's attention and encourage them to visit. This regional tourism promotional video design activity can be a solution in introducing regional tourism and of course developing regional tourism based on folklore